SIX NEW SPECIES OF SYZYGIUM (MYRTACEAE) FROM SUMATRA - Widodo, P.; Chikmawati, T. (Edinburgh Journal of Botany, 2016)
Six new species of Syzygium Gaertn. from Sumatra are described and illustrated. Three are newly described, namely Syzygium abatakum Widodo, S. bengkulense Widodo and S. ketambense Widodo. The descriptions of the other three species, namely Syzygium angustovatum Widodo & Chikmawati, S. comosum Widodo and S. longipetiolatum Widodo are republished to validate their names. The conservation status of each species is proposed, following IUCN guidelines.